PEDAGOGIC INNOVATION: FROM TERMINOLOGICAL REASONING TO JUSTIFYING THE INTTRODUCTION OF CRITERIA - Demyanenko, Nataliia (Continuing Professional Education: Theory and Practice, 2019)
The category of “advanced, exemplary, innovative educational experience” is theoretically substantiated. It is revealed the correlation of the definitions such as “author’s school and “innovative educational technology.” The phenomenon of “implementation” is defined. The evaluation criteria and selection of educational innovation, socio-pedagogical, theoretical and practical, scientific and methodological, moral and psychological conditions for successful implementation of advanced practice teaching experience into schools are developed. It is found the basic steps of the process